Improvement in maternal knowledge, attitudes, and children's weight with education on World Health Organization feeding recommendations - Ulfia Fitriani Nafista; Nani Nurhaeni; Fajar Tri Waluyanti (PAGEPress Publications, 2023)
Malnutrition is among the most common nutritional problems in children worldwide. Specifically, stunting as a malnutrition problem is a global priority, including in Indonesia. This study analyses the effect of nutrition education interventions on maternal feeding knowledge, maternal feeding attitudes and children's weight. A quasi-experimental design using a pre-and post-test was selected and with a total sample of 70 people were assigned to an experimental and control group. This study was conducted in Jember Regency on July 2022, and the instrument used in this research were knowledge, attitude, and practice (KAP) questionnaires from the Food and Agriculture Organization (FAO). A Bivariate analysis showed that the nutritional education intervention had a significant relationship with increased maternal feeding knowledge and attitude and children's weight in the control group and intervention group (p-value <0.05). However, a higher score was on the intervention group score compared to the control group. Meanwhile, the average weight of the children in the intervention group increased by about 331.42 grams, which higher compare to the control group's average weight gain. This study concluded that health education about eating, according to the World Health Organization (WHO) recommendations, through an action-oriented group approach can significantly increase maternal feeding knowledge, attitudes, and children's weight.